Fabrication of a coral/double-wall TiO2 nanotube array film electrode with higher photoelectrocatalytic activity under sunlight. (17th March 2015) - Liu, Yan; Mu, Kangsheng; Yang, Gang; Peng, Hong; Shen, Fei; Wang, Lilin; Deng, Shihuai; Zhang, Xiaohong; Zhang, Yanzong
Abstract : A unique coral/DWNT TiO2 film electrode with a mixed-phase was prepared, and its optical absorption can extend to the visible region. Abstract : A coral/double-wall TiO2 nanotube array (coral/DWNT TiO2 ) film electrode was synthesized via anodic oxidation in an ultrasonic bath in an organic electrolyte containing 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4 ]). The morphology, crystal structure, chemical state, and optical properties of the TiO2 film were characterized via field emission scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy (XPS), and UV-Vis absorption spectroscopy. The results showed that the film had a unique lower layer DWNT/upper layer coral structure with a mixed phase of anatase and rutile. The XPS results proved that the interstitial nitrogen atoms doped in the TiO2 crystal lattice as a Ti–O–N bond. The coral/DWNT TiO2 film exhibited evident absorption in the range of 400 nm to 800 nm and significant photoelectrocatalytic activity under sunlight.